2011
DOI: 10.1038/eye.2011.312
|View full text |Cite
|
Sign up to set email alerts
|

Association of human papilloma virus with pterygia and ocular-surface squamous neoplasia

Abstract: There are more microorganisms that colonize the human body than resident cells; some are commensal whereas others are pathogenic. Pathogenic microorganisms are sensed by the innate or adaptive immune system, an immune response is initiated, and the infection is often cleared. Some microorganisms have developed strategies to evade immune defenses, ensuring their long-term survival with potentially devastating consequences for the host. Approximately 18% of all cancers can be attributed to infective agents; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 95 publications
0
59
0
7
Order By: Relevance
“…6 Pterygium and OSSN share potential common risk factors such as exposure to UVB, chronic ocular surface irritation, or HPV infection. [7][8][9][10] Pterygium and OSSN can coexist. 11 In several studies, it has been suggested that pterygium is a stem cell disorder with premalignant features.…”
Section: Introductionmentioning
confidence: 98%
“…6 Pterygium and OSSN share potential common risk factors such as exposure to UVB, chronic ocular surface irritation, or HPV infection. [7][8][9][10] Pterygium and OSSN can coexist. 11 In several studies, it has been suggested that pterygium is a stem cell disorder with premalignant features.…”
Section: Introductionmentioning
confidence: 98%
“…Par conséquent, il existerait un risque moins important de développer une néoplasie dans les zones peu exposées à ces rayonnements [7][8][9][10]. Outre cette exposition, le ptérygion et les néoplasies malpighiennes de la surface oculaire partageraient d'autres facteurs de risque comme l'infection par le HPV [4,5]. Certains facteurs de risque de ces tumeurs sont retrouvés dans notre observation : l'âge supérieur à 60 ans [1], l'origine du patient, l'exposition aux rayonnements ultraviolets [2], la récidive précoce après chirurgie et le caractère rapidement extensif de la tumeur.…”
Section: Discussionunclassified
“…Les néoplasies malpighiennes de la surface oculaire sont la cause la plus fréquente de tumeurs conjonctivolimbiques malignes et affectent principalement les sujets de plus de 60 ans [1], exposés à des facteurs de risque particuliers dont les principaux sont les rayonnements ultraviolets [2], le virus de l'immunodéficience humaine (VIH) [3], et le human papilloma virus (HPV) [4,5]. Ces tumeurs restent cependant rares [6] et se caractérisent par un important polymorphisme clinique (allant de la lésion asymptomatique jusqu'au tableau de panophtalmie) mimant parfois des lésions bénignes telles qu'un ptérygion.…”
Section: Introductionunclassified
“…Ocular surface squamous neoplasia, that is conjunctival squamous neoplasia, is a highly intersting tumour which is evaluated by Scott et al [2002], Biswas et al [2010], Aktas et al [2012], Chauhan et al [2012], Di Girolamo [2012 as well as by Kao et al [2012].…”
Section: Discussionmentioning
confidence: 99%